ANALISIS LATIHAN KETERAMPILAN MENYIMAK DAN BERBICARA DALAM BUKU “CHINESE MADE EASY I EDISI KEDUA” - Prabowo, Jocelin; Sutandi, Septerianie (PRASI, 2023)
The “Chinese Made Easy” textbook is one of the widely used textbook in learning Mandarin at secondary school in West Java. Apart from the high level of use, this textbook remain has disadvantages, particularly on the aspect of  exercises. This research analyzes and evaluates Chinese listening and speaking skills exercises in “Chinese Made Easy I 2nd Edition” textbook. The purposes of this research were to analyze the suitability of the exercises in the “Chinese Made Easy I 2nd Edition” textbook with the indicators for evaluating exercises designed by Li Quan, as well as to describe its advantages and disadvantages. This research uses a content analysis method with a qualitative approach. Researchers mapped the listening and speaking exercise in “Chinese Made Easy I 2nd Edition” textbook  as data. Data analysis of exercise evaluation indicators is categorized into aspects of learning material coverage, aspects of the number and variety of types of exercises, aspects of levels of difficulty and relevance between exercises, and aspects of motivational function. The results indicate that the exercises in “Chinese Made Easy I 2nd Edition” textbook are quite compatible with the indicators for evaluating exercises. This textbook has exercises that are in accordance to the learning materials, variative, gradual, and can encourage students on developing their listening and speaking skills in Mandarin, yet it has disadvantages in the aspect of the amount and variety of listening exercises. Keywords: Exercises, listening skills, speaking skills, textbook, Chinese Made Easy.   Abstrak Buku “Chinese Made Easy” merupakan salah satu buku ajar yang banyak digunakan dalam pembelajaran bahasa Mandarin tingkat SMP/SMA di Jawa Barat. Terlepas dari tingkat penggunaan yang tinggi, buku ini masih memiliki kekurangan, terutama dalam aspek latihan. Penelitian ini menganalisis dan mengevaluasi latihan keterampilan menyimak dan berbicara bahasa Mandarin pada buku “Chinese Made Easy I Edisi Kedua”. Tujuan dari penelitian ini adalah untuk menganalisis kesesuaian antara latihan pada buku “Chinese Made Easy I Edisi Kedua” dengan indikator evaluasi latihan yang dirancang oleh Li Quan, serta untuk memaparkan kelebihan dan kekurangan dari latihan buku tersebut. Penelitian ini menggunakan metode analisis isi dengan pendekatan kualitatif. Peneliti melakukan pemetaan terhadap soal latihan menyimak dan berbicara buku “Chinese Made Easy I Edisi Kedua” sebagai data. Analisis data terhadap indikator evaluasi latihan dikategorikan ke dalam aspek cakupan materi pembelajaran, aspek jumlah dan variasi jenis latihan, aspek tahapan tingkat kesulitan dan relevansi antarlatihan, serta aspek fungsi motivasi. Hasil penelitian menunjukkan bahwa soal latihan pada buku “Chinese Made Easy I Edisi Kedua” sudah cukup sesuai dengan indikator evaluasi latihan. Buku ini memiliki latihan yang sesuai materi, variatif, bertahap, dan dapat mendorong siswa untuk berlatih mengembangkan keterampilan menyimak dan berbicara bahasa Mandarin, namun memiliki kekurangan dalam aspek jumlah dan variasi latihan menyimak.